Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas, Dan Opini Audit Terhadap Audit Delay Pada Perusahaan Transportasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Yeslika Br Bangun; Ninta Katharina; Eko Deswin Miechaels Siringo-Ringo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The inspiration that drives this examination is to find out the impact of organization size, productivity, dissolvability, and review assessment on review deferral at the transportation association listing the Indonesian Stock Exchange for the period 2020-2022. Any authority utilizes information from the annual budget report obtained by the IDX. The technique for examining utilizes reason examination. The tests used consist of classical assumption tests, specifically normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, panel data regression tests, coefficients (R2), partial hypotheses (T), simultaneous hypotheses (F). Audit Delay is simultaneously significantly influenced by Company Size, Profitability, Solvency, and Audit Opinion. The results of the examination are company parameters, profitability, audit opinion has no impact on audit delay, solvency has an impact on audit delay.